The effects of annealing temperature on structural and optical properties of S-doped ZnO nanobelts - Yousefi, R.; Kamaluddin, B. (Elsevier, 2010)
In this study, the effects of thermal annealing temperature on the structural and optical properties of S-doped ZnO nanobelts were investigated. The XRD pattern shows that the crystallinity of S-doped ZnO nanobelts improves with increased annealing temperature. Room temperature photoluminescence spectroscopy of the as-grown S-doped ZnO nanobelts shows no detectable ultraviolet peak with the broad peaks in the visible emission region at 480, 505, and 518 nm. A weak peak in the ultraviolet region at 383 nm appears after annealing at 400 and 600 degrees C. Raman spectroscopy of the sample also shows a significant change with an increase in the annealing temperature. (C) 2009 Elsevier Masson SAS. All rights reserved.